Teacher's Perception on the Application of Scientific Approach Towards Arabic Learning in Islamic Boarding Schools - Nurlaila, Nurlaila; Kamaluddin, Kamaluddin (Jurnal Al Bayan : Jurnal Jurusan Pendidikan Bahasa Arab, 2019)
The scientific approach has been applied in Arabic learning in schools/madrasah throughout Indonesia over the past few years. However, this is not the case in Islamic boarding schools, not all Islamic boarding schoolsapply this scientific approach in Arabic learning. This research aims to reveal the teacher’s perception of the application of scientific approaches in Arabic learning in Islamic boarding schools. The research method used was a survey method. The research sample consisted of 20 Islamic boarding schools in the province of West Sumatra. Research data were collected through a questionnaire filled out by Arabic language teachers in the Islamic boarding schools. The data analysis technique is descriptive quantitative analysis using percentages. The results showed that the majority of teachers agreed with the application of the scientific approach in Arabic learning in Islamic boarding schools since the majority of teachers perceive that the scientific approach is appropriate and effective to be used in Arabic learning. However, some teachers still find difficulties in implementing it even though they have participated in various trainings. In addition, not all Islamic boarding schools are equipped with adequate infrastructure to support the implementation of a scientific approach.Therefore, it is needed a policy from the authorities to improve teacher competence and complete facilities for the implementation of scientific approach towards Arabic learning in Islamic boarding schools.